Mimic Pork Rinds from Plant-Based Gel: The Influence of Sweet Potato Starch and Konjac Glucomannan - Qibo Zhang; Lu Huang; He Li; Di Zhao; Jinnuo Cao; Yao Song; Xinqi Liu (Molecules, 2022)
This study investigated the effect of sweet potato starch (SPS) and konjac glucomannan (KGM) on the textural, color, sensory, rheological properties, and microstructures of plant-based pork rinds. Plant-based gels were prepared using mixtures of soy protein isolate (SPI), soy oil, and NaHCO3 supplemented with different SPS and KGM concentrations. The texture profile analysis (TPA) results indicated that the hardness, cohesiveness, and chewiness of the samples improved significantly after appropriate SPS and KGM addition. The results obtained via a colorimeter showed no significant differences were found in lightness (L*) between the samples and natural pork rinds after adjusting the SPS and KGM concentrations. Furthermore, the rheological results showed that adding SPS and KGM increased both the storage modulus (G’) and loss modulus (G’’), indicating a firmer gel structure. The images obtained via scanning electron microscopy (SEM) showed that the SPS and KGM contributed to the formation of a more compact gel structure. A mathematical model allowed for a more objective sensory evaluation, with the 40% SPS samples and the 0.4% KGM samples being considered the most similar to natural pork rinds, which provided a comparable texture, appearance, and mouthfeel. This study proposed a possible schematic model for the gelling mechanism of plant-based pork rinds: the three-dimensional network structures of the samples may result from the interaction between SPS, SPI, and soybean oil, while the addition of KGM and NaHCO3 enabled a more stable gel structure.